A Rise in ROS and EPS Production: New Insights into the Trichodesmium erythraeum Response to Ocean Acidification. Issue 1 (20th November 2020) - Wu, Shijie; Mi, Tiezhu; Zhen, Yu; Yu, Kaiqiang; Wang, Fuwen; Yu, Zhigang
Abstract : The diazotrophic cyanobacterium Trichodesmium is thought to be a major contributor to the new N in parts of the oligotrophic, subtropical, and tropical oceans. In this study, physiological and biochemical methods and transcriptome sequencing were used to investigate the influences of ocean acidification (OA) on Trichodesmium erythraeum ( T. erythraeum ). We presented evidence that OA caused by CO2 slowed the growth rate and physiological activity of T. erythraeum . OA led to reduced development of proportion of the vegetative cells into diazocytes which included up‐regulated genes of nitrogen fixation. Reactive oxygen species (ROS) accumulation was increased due to the disruption of photosynthetic electron transport and decrease in antioxidant enzyme activities under acidified conditions. This study showed that OA increased the amounts of (exopolysaccharides) EPS in T. erythraeum, and the key genes of ribose‐5‐phosphate (R5P) and glycosyltransferases ( Tery_3818 ) were up‐regulated. These results provide new insight into how ROS and EPS of T. erythraeum increase in an acidified future ocean to cope with OA‐imposed stress.